Essays on the economics of crime in Mexico - Corona Juárez, Nicolás (2013)
This dissertation looks at the influence of crime on three important aspects of Mexico: The tourism industry, the threat of organized crime towards the Mexican youth and the spread of drug crime throughout the country. Even though crime has long been a present threat for the Mexican economy and society, this research project was motivated by the public security problem being faced by the Mexican Federal Government and the Mexican population since the end of 2006.